Offensive realism and minilateralism in the balkans - Đekić, Aleksandar (National interest, 2025)
This paper analyzes the emergence of new minilateral defense arrangements in the Balkans, focusing on the Tirana and Zagreb Declarations of 2025. Although these initiatives are formally aligned with NATO and EU frameworks and rhetoric, they essentially represent strategic balancing efforts among small states reacting to the perceived shift in regional power and the growing influence of Serbia and its external partners. The study applies the theoretical framework of offensive realism, contrasting it with liberal institutionalism, to explain why states seek narrower, faster, and more controllable security formats even within existing alliances.The analysis demonstrates that minilateralism functions as an operational mechanism within broader institutional structures rather than an alternative to them. In an environment of persistent uncertainty, states turn to selective cooperation formats that enable rapid decision-making, interoperability, and industrial coordination when multilateral institutions appear too slow or ambiguous. The Tirana Declaration, linking Albania, Croatia, and Kosovo, and the Zagreb Declaration, connecting Croatia and Slovenia, reveal a layered response aimed at consolidating capabilities and signaling cohesion under the guise of Euro-Atlantic solidarity. Parallel to this, Serbia’s asymmetric counterbalancing strategy, anchored in defense-industrial cooperation with Hungary, political and symbolic coordination with Russia, and technological and training partnerships with China, illustrates how a non-aligned actor adapts to regional consolidation efforts without directly opposing major institutions. The findings confirm three major propositions. First, offensive realism remains a reliable explanatory framework for state behavior even within heavily institutionalized environments. Second, institutions primarily shape rhetoric and procedural legitimacy but not the actual distribution of power. Third, minilateralism has become an intermediate channel that shortens the time between threat perception and coordinated response. The research concludes that institutions can organize discourse, but power continues to organize reality, and that the persistence of uncertainty inevitably drives states toward new, flexible, and interest-driven security configurations.
Keywords: offensive realism; minilateralism; , Balkan security; Serbia; NATO